2008
DOI: 10.1111/j.1600-051x.2008.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and remodeling of human extraction sockets

Abstract: The present findings demonstrated that great variability exists in man with respect to hard tissue formation within extraction sockets. Thus, whereas a provisional connective tissue consistently forms within the first weeks of healing, the interval during which mineralized bone is laid down is much less predictable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
333
2
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 308 publications
(364 citation statements)
references
References 27 publications
16
333
2
13
Order By: Relevance
“…19 Penelitian sebelumnya menyatakan bahwa anyaman tulang dapat diamati pada 2 hingga 4 minggu setelah ekstraksi gigi. 20 Penelitian lain menunjukkan bahwa terdapat peningkatan hidroksi prolin yang berdampak pada peningkatan kandungan kolagen pada kelinci yang diberi aplikasi gel lidah buaya pada hari ke-7 jika dibandingkan dengan kelompok tanpa perlakuan. 21 Vitamin C yang terkandung di dalam lidah buaya berperan sebagai kofaktor dari hidroksilasi prolin yang dibutuhkan dalam sintesis dan sekresi kolagen.…”
unclassified
“…19 Penelitian sebelumnya menyatakan bahwa anyaman tulang dapat diamati pada 2 hingga 4 minggu setelah ekstraksi gigi. 20 Penelitian lain menunjukkan bahwa terdapat peningkatan hidroksi prolin yang berdampak pada peningkatan kandungan kolagen pada kelinci yang diberi aplikasi gel lidah buaya pada hari ke-7 jika dibandingkan dengan kelompok tanpa perlakuan. 21 Vitamin C yang terkandung di dalam lidah buaya berperan sebagai kofaktor dari hidroksilasi prolin yang dibutuhkan dalam sintesis dan sekresi kolagen.…”
unclassified
“…A recent study by Morgan (2012) found that it takes at least 29 weeks in humans for sockets to be fully healed, which was defined on the basis of bone presence throughout the cavity left by tooth extraction (Morgan, 2011). Other research has found variability in the early phases of bone remodeling in humans (Trombelli et al, 2008), which implies that the rate and duration of remodeling of the alveolar sockets may vary between individuals. Whether there is a difference in alveolar resorption between adjacent teeth extracted simultaneously is at present unknown.…”
Section: Methodsmentioning
confidence: 98%
“…Le tissu de granulation va progressivement se transformer en tissu conjonctif fibreux pendant que la formation osseuse se poursuit avec l'apparition des trabécules minéralisées dès la 3 e semaine suivant l'extraction dentaire. À partir de la 15 e semaine l'alvéole est comblée par un tissu osseux minéralisé même si l'organisation de l'architecture osseuse n'est pas complète avant 24 semaines [1][2][3].…”
Section: Introductionunclassified